The Tele-Learning Airport Model: Serving Consumer and Producer Students - Dobozy, Eva; Reynolds, P. (IADIS Press, 2012)
In response to global pressures to increase the adoption of eTeaching and Learning (eTL) provisions in higher education in the coming years, motivated by economic and/or pedagogical considerations, universities are increasing their efforts to offer interactive, collaborative and deeply engaging learning experiences for students that are infused with and mediated by Web 2.0 applications. In this paper, we argue, that this process brings to the surface increased recognition that many eTL systems and applications are still raw, but above all, poorly understood by many lecturers and students. To assist the conceptualisation of the interrelationship between various eTL systems, belonging to different generations of eTL, we developed the tele-learning airport model. This model is based on metaphoric reasoning, providing a language to describe the principles of eTL systems and users' primary practices. Moreover, our model is able to make explicit the blurring of lines between various generations of eTL, their functionality and more importantly, attractiveness to users for particular pedagogical purposes.